Study of Participation of Women In Life Insurance (International Journal of Food and Nutritional Sciences, 2022)
Women occupied around 49 per cent of the total population in India. Their contribution to the economic activity of the country is slightly increasing every year and it is important. Under the situation, there is a need for life insurers to accept the growing importance of women population in the economy, identify their special needs or requirements, if any, and develop suitable product solution to provide adequate life insurance coverage. In this context, a short study is made on the share of female lives covered in life insurance business. Only discrete new business data- number of policies and first year premium for the year 2021-22 has been considered for the purpose.